(untitled) (Revista Educação, Artes e Inclusão, 2024)
This article is configured as a section of completed graduate research and aims to reflect on the use of the Libras Visual and Hand Talk applications in the literacy process of a child with deafness in Early Childhood Education, in a public school in the city. from the city of Areia Branca / RN. For that, we present the Apps to the student and teachers of the school; we develop literacy activities from a bilingual teaching perspective and we apply activities to the student, developed collaboratively. The methodology adopted in this investigation is characterized as qualitative materialized in the activities carried out with the student, as well as in the conduct of an interview with the collaborating teachers. Based on the theoretical conceptions of Skliar (1998), Vygotsky (1997), Karnopp (2015), Kenski (2008), among others, we come to the conclusion that the presented applications are configured as potentializing tools that assist in the teaching and learning process of a deaf child in the context of literacy.